Erratum: Altomare et al. In-Depth AGE and ALE Profiling of Human Albumin in Heart Failure: Ex Vivo Studies. Antioxidants 2021, 10, 358 - Alessandra Altomare; Giovanna Baron; Marta Balbinot; Alma Martínez Fernández; Alessandro Pedretti; Beatrice Zoanni; Maura Brioschi; Piergiuseppe Agostoni; Marina Carini; Cristina Banfi; Giancarlo Aldini (MDPI AG, 2021)
The authors of this paper [...]